Orofacial pain and its relation with hypocalcemia associated with chronic kidney disease: an overlook differential diagnosis (Research, Society and Development, 2021)
Although orofacial pain is a condition of multifactorial etiopathogenesis and sometimes it is difficult to diagnose it, a possible cause for this condition is muscle changes, which in turn can originate in systemic conditions, such as hypocalcemia. The present article aims to present a clinical situation of orofacial pain due to hypocalcemia in a young female patient with chronic kidney disease. The patient attended hospital care with strong pain complaints in the face, being evaluated by the Maxillofacial Surgery team and the Neurology medical team, without the precise determination of an etiology. Despite being prescribed oral medication, the patient returned with the complaint of pain and with a new symptom of cramping in the face, in face of that, hematological tests were requested where hypocalcemia condition was found. The therapeutic approach consisted of oral calcium supplementation, which was sufficient to suppress facial complaints. It is concluded that there is a correlation between blood calcium concentration and muscle changes in the face, requiring clinical studies that better explain this relationship.